Penyembuhan Luka Sayat menggunakan Gel Ekstrak Bawang Batak (Allium Chinense G. Don) : Studi Eksperimen pada Tikus Putih - Edward Waroka; Surya Dharma; Edy Fachrial (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
The primary function of skin is to protect the inside of the body from physical and mechanical stresses. Skin is perceptive to its surroundings. Thus, a variety of skin issues may develop, including wounds. The standard wound treatment is chemical therapy using antiseptics. Antiseptics contain antimicrobial qualities that can eradicate bacteria. However, antiseptics can also destroy fibroblast tissue, which creates new skin tissue, and leukocytes, which are responsible for eliminating harmful bacteria. Alternative medicines, such as traditional medicine, are thus required to aid in wound healing. The purpose of this research is to determine the effectiveness of Allium chinense G. Don extract on the healing of cut wounds in white rats. This research is experimental research using a post-test control group design. Data analysis used One way ANOVA. The research found that Allium chinense G. Don extract contained alkaloids, flavonoids, saponins, and triterpenoids/steroids, but no tannin compounds. The antibacterial properties of Allium chinense G. Don are effective against Pseudomonas aeruginosa and Staphylococcus aureus bacteria. Collagen density and fibroblast count increased in Wistar rat wound tissue after being treated with the extract. Allium chinense G. Don is effective in healing cut wounds in white rats (p <0,001).